Getting a Grip on Climate Change in the Philippines : Executive Report - World Bank (Washington, DC, 2014)
The Philippines already experiences and will continue to face impacts from climate change. In the decades ahead, the most serious consequences will be felt in coastal and urban areas. Severe hardships are expected in agriculture and fisheries, leading to negative impacts on jobs and the economy. With these risks in mind the Philippine Government has initiated significant climate reforms, establishing a basis for transformation. To assess gaps and accelerate implementation of the climate reform agenda, in 2012 the Department of Budget and management and the climate change commission sought advisory services from the World Bank to carry out a Climate Public Expenditure and Institutional Review (CPEIR). Carried out at mid-term of the first phase of the national climate change action plan, the Philippine development plan (2011-2016), and the current administration, this review comes early enough to help guide the finalization and operationalization of the first phase of the climate reform agenda. This executive report summarizes the findings and recommendations of the CPEIR, including an analytical snapshot of the policies, institutions, and expenditures for undertaking climate action in the Philippines, and recommendations to contribute to a successful implementation of the Philippine climate reform agenda.